Analisis Kebijakan Kawasan Ekonomi Khusus Sorong sebagai Kawasan Industri Nikel di Papua - Muzwardi, Ady; Nurhayati (Universitas Cenderawasih, 2025)
Indonesia has been establishing Special Economic Zones (SEZs) across the country, with the Sorong SEZ being one of them. The Sorong SEZ is expected to become the first new center of economic growth in the Papua region. Several potential sectors include agriculture, fisheries, forestry, tourism, creative industries, and other natural resource utilization. This article aims to examine the effectiveness of the Sorong SEZ and to explore its implications for Indonesia and the wider region. It argues that the establishment of the Sorong SEZ is not only effective due to support from both regional and central governments but also offers significant geoeconomic and geostrategic benefits. In terms of geoeconomic advantages, the Sorong SEZ not only fosters regional economic development in eastern Indonesia and serves as a center for natural resource processing in Papua, but also functions as a gateway for trade in the Asia-Pacific region. From a geostrategic perspective, it strengthens Indonesia's sovereignty and cross-border economic diplomacy with Papua New Guinea and is expected to attract increased foreign investment, particularly China, due to its strategic location bridging Asia and Pacific. KEYWORDS Geoeconomics; Geostrategy; Sorong; Special Economic Zone